Pemilihan Supplier Material Baja untuk Proyek Tower Menggunakan Metode Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) di PT. XSF - Hady Sofyan, Hady Sofyan; Yansa Nur Sany; Haris Sandi Yudha (Jurnal Teknologika, 2023)
. Determining suppliers for procurement of goods is a complex task because many criteria must be considered and some criteria are difficult to judge. Changes in supplier performance and lack of available information can complicate decision making. Selection of the right supplier can help reduce operational costs, increase profits and product quality, increase competitiveness in the market, and meet customer needs efficiently. Therefore, the purpose of this research is to develop a method that can assist practitioners in selecting suppliers logically, especially in situations of uncertainty and/or lack of information. Implementation of the multi-criteria decision making (MCDM) method is used to select the best solution based on predetermined criteria. One of the MCDM methods that can be used is the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), which was selected in several Multiple Attribute Decision Making (MADM) models because the concept is simple and easy to understand, and has several advantages. This research was conducted at a steel structure engineering and fabrication company where one of the products produced was steel construction for bridges, towers, and fabrication. The main material used is elbow steel. Due to the large number of suppliers who can provide goods, this research examines the selection of angle steel suppliers for the company's main material. The results of TOPSIS calculations in supplying the main raw materials are suppliers of PT. KW with regard to 4 criteria, namely Quality, Delivery, Warranty and Claim Policy, and Price.